Uwagi o znakach własnościowych z drugiej połowy XV i pierwszej ćwierci XVI wieku w inkunabułach Biblioteki Uniwersyteckiej w Poznaniu - Wagner, Arkadiusz (Biblioteka Uniwersytecka w Poznaniu, 2013)
Artykuł stanowi zbiór uwag dotyczących charakterystycznych kategorii znaków własnościowych książki, znajdujących się w inkunabułach ze zbiorów Biblioteki Uniwersyteckiej w Poznaniu, osadzonych na tle zjawisk kulturowych późnego średniowiecza i początków renesansu w Europie i w Polsce. Analizie poddane zostały: ekslibris malowany (protoekslibris), rysunkowy model ołtarza z herbem fundatora wklejony do książki jako przedmiot dewocji i prawdopodobnie znak własności, tzw. superekslibris zapięciowy umieszczony na zaczepie zapięcia oprawy, nazwiska właścicieli ksiąg zapisane na okładzinach opraw, herby rysowane na stronach tytułowych. Osobną uwagę poświęcono ekslibrisom graficznym, w tym zwłaszcza unikatowym dziełom związanym z anonimowym bibliofilem herbu Rawicz, oraz ekslibrisom odbijanym bezpośrednio na kartach ksiąg.

This article reports on a set of remarks on the characteristic types of private ownership marks that are to be fund in the incunabula currently held in the collection of old and rare books at Poznań University Library. The marks of ownership are analyzed and positioned against the cultural phenomena of the late Middle Ages and early decades of Renaissance in Europe and Poland. First, the hand-painted bookplate (the earliest form of book plates) is discussed. This analysis is then followed by descriptions of the sketched altar model (bookplate depicting an altar) with the coat-of-arms of the donator pasted into a book as an object of devotion and, presumably, a proper mark of ownership, then the so-called clasp hasp bookplate (in German language: Schließen-Exlibris), placed on the hasp of the clasp on the binding. Finally, names inscribed on the inside front cover of a book that indicated its owner or owners, and individual family crests placed on title pages are discussed. Separate attention is given to graphical bookplates, in particular to unique pieces of ornamentation that relate to the anonymous book collector with the exhibited noble Rawicz coat of arms, as well as to book plates imprinted directly onto pages of books.
Some remarks on the private marks of ownership of books from the latter half of the fifteenth century and the first decades of the sixteenth century in the incunabula kept at Poznań University Library
Keywords: ekslibris malowany; painted bookplate; superekslibris zapięciowy – Schließen-Exlibris; clasp book plate – Schließen-Exlibris; herb; crest; Piotr Wedelicjusz z Obornik; prymas Stanisław Karnkowski; Anonim „L G” herbu Rawicz